Co-creation Workshop Report Ghana: 2030 VISION AND ROLE OF SECTOR GROUPS IN MAINSTREAMING CLIMATE SMART COCOA VALUE CHAINS - Dalaa, Mustapha Alasan; Asare, Richard; Jassogne, Laurence T.P. (2017)
The workshop was jointed facilitated by RA and IITA. Christian Mensah of RA welcome all participant and gave the welcome remarks. In his introductory remarks, he updated participants on the several activities the project was working on and highlighted the need not to over concentrate /emphaze on the only the CSA practices though important but also to work collectively towards creating a desired future outcome to benefit the people at the center cocoa cultivation, cocoa farmers and its associated value chain actors (public institutions and private companies)